2000
DOI: 10.1890/1051-0761(2000)010[0744:gdibas]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Gap Dynamics in Boreal Aspen Stands: Is the Forest Older Than We Think?

Abstract: Trembling aspen (Populus tremuloides) in western Canadian boreal forests is generally believed to occur as young, even‐aged stands, as part of a fire‐dominated landscape. However, the available quantitative estimates of the rate of disturbance by fire in this region differ markedly. One estimate is consistent with forests much older than are currently thought to exist. The theory of gap dynamics may partly reconcile the discrepancy, by suggesting a mechanism whereby old, uneven‐aged aspen stands could develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…4) are concentrated along the north shore of Lake Ontario on the Oak Ridges Moraine, on the Frontenac Arch of ancient shield rock along the St. Lawrence, and on the Awenda Peninsula at the south end of Georgian Bay. It should be noted that the FRI estimates the predominant age of dominant canopy species, and the forest may actually be older than this (Cumming et al 2000).…”
Section: Current Status Of Old Growth In Southern Ontariomentioning
confidence: 99%
“…4) are concentrated along the north shore of Lake Ontario on the Oak Ridges Moraine, on the Frontenac Arch of ancient shield rock along the St. Lawrence, and on the Awenda Peninsula at the south end of Georgian Bay. It should be noted that the FRI estimates the predominant age of dominant canopy species, and the forest may actually be older than this (Cumming et al 2000).…”
Section: Current Status Of Old Growth In Southern Ontariomentioning
confidence: 99%
“…The usual model of succession for the mixedwood describes a relatively pure aspen stand establishing after disturbance, with white spruce gradually developing in the understory, leading to a relatively pure white spruce stand after many decades (see Cumming et al 2000, for a current review). However, reforestation standards for the coniferous land base mandate the rapid establishment of a pure coniferous stand.…”
Section: Steven Cummingmentioning
confidence: 99%
“…Third, although fire return intervals typical of the boreal mixedwood forest are several times longer than the average lifetime of an individual Ovenbird, it seems reasonable to expect that since the last glaciation, Alberta Ovenbird has evolved in a more patchy landscape containing large burned areas with scattered unburned stands, whereas Ovenbird from the temperate forest of southern Québec has evolved in a landscape characterized by small, scattered, non-forest gaps such as small bogs, rocky outcrops, blowdowns, and treefall gaps. Because stands sometimes escape fire and reach old age even in the boreal mixedwood forest (Cumming et al 2000), we assumed that mature and old stands were available to Ovenbird throughout the time period considered.…”
Section: Introductionmentioning
confidence: 99%
“…Smyth et al (2005) surveyed uplands similar to those occupied by Ovenbird and reported that, on average, live trees cover 26% of the area subject to wildfires. Cumming et al (2000) have also documented the occurrence of gap-phase dynamics in the boreal mixedwood forest of Alberta, with gaps occupying 4-17% of stands surveyed. Thus, the natural disturbance regime of the boreal mixedwood forest does produce a structurally complex mosaic, but we submit that the coarse-grained structure created by fires in boreal Alberta cannot possibly be matched by the natural disturbance regimes that have characterized the Québec region in the recent or distant past.…”
Section: Introductionmentioning
confidence: 99%